Anticryptococcal resistance in the mouse brain: beneficial effects of local administration of heat-inactivated yeast cells. - Blasi, E (1994)
Using a murine model, we have previously shown that brain resistance to local infection with opportunistic fungi is affected by manipulation of the host myelomonocytic compartment. Here, we demonstrate that intracerebral administration of heat-inactivated Cryptococcus neoformans (H-CN) yeast cells results in a consistent enhancement of mouse survival to subsequent local challenge with lethal doses of C. neoformans. The phenomenon, more pronounced upon double H-CN treatment, is associated with (i) massive local inflammatory response, (ii) reduced growth of the fungus within the brain, and (iii) induction of delayed-type hypersensitivity. Moreover, H-CN treatment confers protection against local heterologous challenges. Our data provide initial evidence that intracerebral administration of H-CN results in the establishment of aspecific and specific immune responses; the mechanisms of elicitation and relative contributions to host antimicrobial resistance remains to be elucidated.